Two Propagation Scenarios of Isolated Breakdown Lightning Processes in Failed Negative Cloud‐to‐Ground Flashes. Issue 23 (4th December 2020) - Kolmašová, Ivana; Santolík, Ondřej; Defer, Eric; Kašpar, Petr; Kolínská, Andrea; Pedeboy, Stéphane; Coquillat, Sylvain
Abstract: Isolated breakdown process (also known as attempted leader or inverted intra‐cloud discharge) is a lightning phenomenon characterized by radio wave pulses similar to signatures of preliminary breakdown before negative cloud‐to‐ground flashes, but in this case no cloud‐to‐ground return strokes occur. We identified 128 isolated breakdown pulse trains in measurements collected in the Mediterranean by a broadband receiver (0.005–37 MHz) in 2015 and 2018. By combining these records with concurrent Lightning Mapping Array measurements of very high frequency radiation (60–66 MHz) emitted by in‐cloud discharges we investigate the development of each discharge. We identify two scenarios: Either the discharges continue to propagate almost horizontally for more than 150 ms (73%), or they quickly fade out (27%). The geo‐localized sources of the observed isolated breakdown pulse trains, together with their waveform characteristics (duration, inter‐pulse intervals, regularity, and bipolar shapes) show that both scenarios are similar to initiation processes preceding negative cloud‐to‐ground flashes. Plain Language Summary: Visible lightning return stroke represents a well‐known manifestation of atmospheric electricity. However, it is only the last stage of a complex sequence of phenomena that starts inside an electrically charged thundercloud by a preliminary breakdown process, continues by a stepped leader that moves electrical charges into the lightning channel, neutralized eventually by a large return stroke current and followed in most cases by processes leading to subsequent strokes. All these phenomena occurring inside or below the thundercloud involve impulsive electrical currents and hence emit radio waves. Analysis of our observations of isolated breakdown radio wave pulses which are not followed by a return stroke shows that the underlying processes are similar to a usual preliminary breakdown preceding negative cloud‐to ground discharges. Nevertheless, a strong positive charge layer at the bottom of the thundercloud can force the breakdown current pulses to keep flowing inside the cloud or die out and thus prevents them from evolving into a return stroke that would move the negative charge from the cloud to the ground. Key Points: Preliminary breakdown radio wave pulses typical for negative cloud‐to‐ground flashes are exceptionally observed without return strokes Data show evidence of two possible propagation scenarios: The discharge leader either extends horizontally inside the cloud or fades out The first analysis of a large number of events shows that waveform characteristics of pulse trains are very similar for both scenarios